HYDROCHEMISTRY OF GROUNDWATER IN GEYER, GROBOGAN PROVINCE, CENTRAL JAVA - T. Listiyani R.A. (KURVATEK, 2016)
The demand of clean water as well as good quality of drinking water in research area puss the author for knowing about groundwater quality in research area. The aim of the research is to understand the hydrochemistry of groundwater in study area, includinghydrochemical processes and the influence of minerals or rocks to groundwater quality. The methods in the research are groundwater and rocks sampling, petrography and also groundwater’s chemical analysis.Result of this study shows that groundwater quality in Geyer area is influenced by minerals and rocks in that place with dissolution and ions exchange would be important processes. Minerals which composed rocks are dominated by calcareous and clay minerals. These minerals supply chemical components such as Ca2+, Mg2+, Na+, Cl-, carbonate and bicarbonate to groundwater.  Key words: hydrochemistry, groundwater, hydrochemical process, major ion.